ERYSIPELAS IN A CAT-BITE VICTIM CAUSED BY PASTEURELLA MULTOCIDA - CASE REPORT - Gvozdenović, Eleonora; Malinić, Jovan; Nikolić, Nataša; Katanić, Nataša; Jovanović, Milica; Dulović, Olga (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: Erysipelas is a characteristic form of acute superficial streptococcal cellulitis, usually treated in outpatient service, primarily with penicillin, or erythromycin, in cases where the patient is allergic to penicillin. We are reporting the case of a patient who was preventively treated with erythromycin, after a cat bite, but during treatment developed erysipelas, which, after a swab sample from the wound was analyzed, proved to be caused by Pasteurella multocida, resistant to erythromycin. Case report: A 53-year-old woman came to the outpatient clinic with clinical signs of erysipelas cruris. Seven days before, she had been bitten by her own cat. The wound was surgically treated, and erythromycin, 500 mg qid, was prescribed as prophylaxis of wound infection. There were no signs of infection. On the 5th day following the bite, the patient was running a very high fever (39.2°C), but she was without other symptoms, thus the fever was considered to be a symptom of the flu. On the following day, prominent erythematous swelling appeared around the site of the wound, with localized lymphangitis and regional lymphadenitis, and discharge from the wound. The diagnosis of erysipelas was made. The peripheral blood test results were as follows: WBC = 13.9 x 109/l; NE = 82%, CRP = 43 IU. A swab sample was collected from the wound and the patient was started on penicillin. On the 7th day of penicillin administration, there were no signs of inflammation, while the blood test results were as follows: WBC = 5.1 x 109/l; NE = 52%; CRP = 24 IU. Pasteurella multocida, resistant to erythromycin but sensitive to penicillin was isolated from the swab sample. Conclusion: Erysipelas, although an easily recognized clinical entity, can be caused by other microorganisms, besides streptococcus. It is very important to consider this in order to make an accurate diagnosis and prescribe the appropriate therapy.